Induction of Apoptosis and Cytotoxic Activities of Iranian Orthodox Black Tea Extract (BTE) Using in vitro Models - Amirala Aghbali; Faranak Moradi Abbasabadi; Abbas Delazar; Sepideh Vosough Hosseini; Fatemeh Zare Shahneh; Behzad Baradaran; Maryam Janani (Tabriz University of Medical Sciences, 2014)
Purpose: Plant-derivate therapeutic agents can perform cancer chemotherapeutic activity through triggering apoptotic cell death. Our aim was to investigate the cytotoxic effects, induction of apoptosis, and the mechanism of cell death of Iranian orthodox black tea extracts (BTEs) and hydro methanolic purified fractions (40, 60, 80 and 100%) in KB cells (oral squamous cell carcinoma). Methods: In order to analyze the cytotoxic activity of the BTEs, MTT (3-(4, 5- dimetylthiazol-2-yl)-2, 5 diphenyltetrazolium bromide) and Trypan-blue assays were performed in oral squamous cell carcinoma (KB). Furthermore, the apoptosis inducing action of the extracts was determined by TUNEL, DNA fragmentation and cell death detection analysis. Results: Dichloromethane BTE and hydro methanol fractions (40 and 60%) extract showed no cytotoxic effects; however, hydro methanol crude and hydro methanol fractions of BTE (80 and 100%) significantly inhibited cell growth and viability in a dose and time dependent manner. In addition, Cell death assay, TUNEL, and DNA fragmentation indicated induction of apoptosis by hydro methanol 80 and 100% fractions of BTE in KB cells. Statistical significance was determined by analysis of variance (ANOVA), followed by Duncan test and p value ≤0.05 was considered significant. Conclusion: The results from the present study suggests that the hydro methanol crude and hydro methanol fractions of BTE (80 and 100%) are significant source of compounds with the anti proliferative and cytotoxic activities, and this may be useful for developing potential chemo preventive substances.